Strategi Supervisi Kepala Sekolah pada Pelaksanaan Pembelajaran Daring di SMAN 1 Baitussalam Aceh Besar - Tihalimah Tihalimah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The purpose of this research is to find out the form of the principal's planning for online learning, the principal's supervisory strategy in implementing online learning, and the obstacles that occur in supervising the implementation of online learning at SMAN 1 Baitussalam. The type of research used is qualitative research with a descriptive approach. The research subjects were the principal, two teachers and one student. Data collection techniques through observation, interviews and documentation. The results of the study show that: first, the principal has prepared a plan before the implementation of online learning begins, the plan is adapted to the concept of virtual learning. Second, the school principal supervises the implementation of online learning using various strategies, starting from supervision techniques, supervision models and supervision approaches. Third, the obstacles that occur in the supervision of school principals in the implementation of online learning, are: (1) time load in carrying out the principal's managerial duties and responsibilities, (2) the teacher's lack of knowledge about the use of technology, (3) some students do not have learning media complete online. The supervision strategy carried out by the school principal is good, but there are still limitations in supervising their students.